Developments in the field of allergy mechanisms in 2015 through the eyes of Clinical & Experimental Allergy. Issue 10 (29th September 2016) - Roberts, G.; Boyle, R.; Bryce, P. J.; Crane, J.; Hogan, S. P.; Saglani, S.; Wickman, M.; Woodfolk, J. A.
Summary: In the first of two papers we described the development in the field of allergy mechanisms as described by Clinical and Experimental Allergy in 2015. Experimental models of allergic disease, basic mechanisms, clinical mechanisms and allergens are all covered. A second paper will cover clinical aspects.